Analisis Penyusunan Anggaran Organisasi Pemerintah di Kelurahan Kendangsari Kota Surabaya - Angelia Fortunata Arisman; Nurul Ainun Nafisah; Mayzura Rahma Aulia Putri; Masyaila Laurensia Zuhri; Galuh Candra Mustika Dewi; Fajar Syaiful Akbar (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
The Regional Revenue and Expenditure Budget (APBD) is the main instrument for organizing and allocating funds to achieve regional development goals. The APBD cycle consists of planning, implementation, administration and accountability stages. This study aims to analyze the process of budget preparation, implementation and accountability in Kendangsari Village, Tenggilis District, Surabaya, with a focus on the application of the Government Resource Management System (GRMS). The preparation of the Regional Revenue and Expenditure Budget (APBD) at the kelurahan level has special characteristics because it involves planning and allocating funds tailored to the needs of the local community and local government development priorities. This research uses descriptive qualitative methods with data collection techniques through interviews, observations, and documentation studies. The results showed that the use of GRMS at the kelurahan level helped improve the accuracy of budget planning, accelerate the process of monitoring budget realization, and facilitate budget reporting and supervision.